Compliance of Nutrient Claims with Nutrition Labelling Standards in Packaged Bakery Products - Prabhjot Kaur; Monika Choudhary; Prabhdeep Kaur (Archives of Current Research International, 2024)
Aim: Nutrition claim means any representation which states, suggests or implies that a food has particular nutritional properties including but not limited to the energy value and to the content of protein, fat and carbohydrates, as well as the content of vitamins and minerals. Consumers may perceive foods carrying nutrition-related claims more positively because of the presence of a claim. However, sometimes the products may not be complaint with their nutrient claims. Place and Duration of Study: The study was carried out in Ludhiana, between 2021-2022. Methodology: In the present study, the packaged bakery products with nutrient claim (7 products) were selected from Ludhiana market and their complacency was evaluated in three phases- 1) Nutrient profiling through nutrition label on packaging 2) Nutrient content claims 3) Nutrient comparative claims. Results: The findings of the study revealed that the selected products such as Cornflake Biscuit, Max Protein cookies, Brownie, Sugar free cookies, Light biscuit, Whole wheat Biscuit and Brown bread were found with nutrient claims such as “rich in fiber”, “trans-fat free”, “cholesterol free”, “rich in protein”, “10g protein”, “4g fibre”, “contains calcium”, “no trans-fat”, “21g protein”, “rich in iron”, and “contains 6 vitamins”. In cornflake biscuits, data regarding nutrient comparative claims showed that the product without nutrition claim contained protein content (2.5g/100g) at par with the product with nutrition claim (2.3g/100g) while, dietary fiber content was significantly (p<0.05) lower in the former (0.98g/100g) as compared to later product (3.98g/100g). The laboratory analysis of max protein cookies showed that protein was present in cookies with a nutrition claim, indicating compliance of this product. However, the value (5.21g/100g) did not meet claim criteria value (10g/100g). Further, the product was compliant in term of claims related to fibre and calcium but the analyzed values such as 2.98g and 280mg per 100 g were found significantly lower (p<0.05) than the claim criterion. Most of the nutrient content claims related to protein and fibre did not meet information on the nutrition label, otherwise the selected products were compliant in terms of nutrition claims. Conclusion: In terms of nutrient content claims, the values of the nutrients obtained through laboratory analysis did not meet the claimed values on nutrition label. Therefore, further studies should focus on evaluating the prevalence and compliance of claims on foods with health or nutrition claim as consumers may perceive them as healthy.